2021
DOI: 10.1245/s10434-021-10385-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Axilla Following Neoadjuvant Endocrine Therapy

Abstract: Background. Randomized clinical trials support deescalation of axillary surgery in breast cancer patients with lowvolume axillary disease treated with a surgery-first approach. However, few data exist to guide axillary surgery following neoadjuvant endocrine therapy (NET). Therefore, we evaluated the extent and outcomes of axillary surgery in a contemporary cohort of NET patients, a treatment approach that has become particularly relevant during the coronavirus disease-19 (COVID-19) pandemic. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The pathological response of the axilla (20%) was higher compared to pathological response rate of the breast. This aligns with previous studies, reporting a nodal pathological response after NET ranging from 4.8% to 13% [ [31] , [32] , [33] ]. Given our relative small sample size these results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pathological response of the axilla (20%) was higher compared to pathological response rate of the breast. This aligns with previous studies, reporting a nodal pathological response after NET ranging from 4.8% to 13% [ [31] , [32] , [33] ]. Given our relative small sample size these results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 93%
“…A review conducted by Weiss et al demonstrated that in 10–50% of the patient remaining node-positive after NET, no ALND was performed [ 40 ]. One of these studies reported 17% of the clinical N1 patients undergoing only sentinel node biopsy, with no regional recurrences reported after a median follow up of 35 months [ 32 ]. In our study, none of the patients who remained node-positive underwent an ALND, instead they were all treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 66 Similarly, Murphy et al reported successful selective de-escalation of axillary surgery in breast cancer patients treated with NET. 80 …”
Section: Resultsmentioning
confidence: 99%
“… The patients were satisfied with telemedicine. Murphy et al, USA 80 Observational study 2008–2019 186 (66 years) Surgical management of axilla following NET Selective de-escalation of axillary surgery was done effectively in breast cancer patients treated with NET in the same way as the current way of treating first with surgery. Breast cancer patients receiving NET can be managed safely by adopting the same way as patients with similar tumours treated with a surgery-first approach.…”
Section: Resultsmentioning
confidence: 99%
“…This occurred for patients with who presented with both clinically nodenegative and clinically node-positive disease and who were found to have limited axillary nodal disease (1 to 2 positive nodes) at surgery after NET. 4 Across both groups, omittance of axillary dissection or axillary radiation or both was not associated with axillary nodal relapse. This indicates that thoughtful extrapolation to the NET setting of reduced axillary treatment is appropriate.…”
Section: Presentmentioning
confidence: 95%